Altered Structural and Functional Connectivity of Juvenile Myoclonic Epilepsy: An fMRI Study - Chengqing Zhong; Rong Liu; Cheng Luo; Sisi Jiang; Li Dong; Rui Peng; Fuqiang Guo; Pu Wang (Neural Plasticity)
The aim of this study was to investigate the structural and functional connectivity (FC) of juvenile myoclonic epilepsy (JME) using resting state functional magnetic resonance imaging (rs-fMRI). High-resolution T1-weighted magnetic resonance imaging (MRI) and rs-fMRI data were collected in 25 patients with JME and in 24 control subjects. A FC analysis was subsequently performed, with seeding at the regions that demonstrated between-group differences in gray matter volume (GMV). Then, the observed structural and FCs were associated with the clinical manifestations. The decreased GMV regions were found in the bilateral anterior cerebellum, the right orbital superior frontal gyrus, the left middle temporal gyrus, the left putamen, the right hippocampus, the bilateral caudate, and the right thalamus. The changed FCs were mainly observed in the motor-related areas and the cognitive-related areas. The significant findings of this study revealed an important role for the cerebellum in motor control and cognitive regulation in JME patients, which also have an effect on the activity of the occipital lobe. In addition, the changed FCs were related to the clinical features of JME patients. The current observations may contribute to the understanding of the pathogenesis of JME.